Metabolic signature and proteasome activity controls synovial migration of CDC42hiCD14+ cells in rheumatoid arthritis - Malmhäll-Bah, Eric; Andersson, Karin M.E.; Erlandsson, Malin C.; Silfverswärd, Sofia T.; Pullerits, Rille; Bokarewa, Maria I. (Frontiers in Immunology, 2023)
Objective Activation of Rho-GTPases in macrophages causes inflammation and severe arthritis in mice. In this study, we explore if Rho-GTPases define the joint destination of pathogenic leukocytes, the mechanism by which they perpetuate rheumatoid arthritis (RA), and how JAK inhibition mitigates these effects. Methods CD14+ cells of 136 RA patients were characterized by RNA sequencing and cytokine measurement to identify biological processes and transcriptional regulators specific for CDC42hiCD14+ cells, which were summarized in a metabolic signature (MetSig). The effect of hypoxia and IFN-γ signaling on the metabolic signature of CD14+ cells was assessed experimentally. To investigate its connection with joint inflammation, the signature was translated into the single-cell characteristics of CDC42hi synovial tissue macrophages. The sensitivity of MetSig to the RA disease activity and the treatment effect were assessed experimentally and clinically. Results CDC42hiCD14+ cells carried MetSig of genes functional in the oxidative phosphorylation and proteasome-dependent cell remodeling, which correlated with the cytokine-rich migratory phenotype and antigen-presenting capacity of these cells. Integration of CDC42hiCD14+ and synovial macrophages marked with MetSig revealed the important role of the interferon-rich environment and immunoproteasome expression in the homeostasis of these pathogenic macrophages. The CDC42hiCD14+ cells were targeted by JAK inhibitors and responded with the downregulation of immunoproteasome and MHC-II molecules, which disintegrated the immunological synapse, reduced cytokine production, and alleviated arthritis. Conclusion This study shows that the CDC42-related MetSig identifies the antigen-presenting CD14+ cells that migrate to joints to coordinate autoimmunity. The accumulation of CDC42hiCD14+ cells discloses patients perceptive to the JAKi treatment.